MicroRNA expression profile in isolated circulating tumor cells in colorectal cancer - O. I. Kit; I. A. Novikova; N. N. Timoshkina; D. Yu. Gvaldin; A. A. Pushkin; O. Yu. Kaimakchi; A. A. Maslov; A. V. Shaposhnikov (Успехи молекулярной онкологии)
Introduction. Colorectal cancer is a frequently diagnosed disease being in the third place among oncological diseases both in incidence and mortality. Currently, researchers focus on development of more accessible and reliable biomarkers of colorectal cancer to overcome the problems in diagnosis and progression prognosis of this pathology.Aim. To investigate characteristics of microRNA expression in circulating tumor cells (CTC) of patients with colorectal cancer. Materials and methods. The study included blood samples from 299 patients with colon cancer, stages II (T3–4N0M0), III (T1–4N1–2M0) and IV (T1–4N0–2M1). Circulating tumor cells were identified using EpCAM marker detection system. Relative expression of hsa-let-7i-5p, hsa-miR-126-5p, hsa-miR-143-3p, hsa-miR-21-5p, hsa-miR-25-3p, hsa-miR-26a-5p, hsa-miR-92a-3p micro RNA in CTC was measured using polymerase chain reaction.Results. Positive CTC status was observed in 188 (62.9 %) of 299 patients, negative in 111 (37.1 %). In the patient group with pT1–2 tumors, the majority of patients did not have CTC (53.3 %). In other patients with pT1–2 disease, the number of CTC was 1.2 and 4.4 times lower than in patients with pT3 and pT4 disease, respectively. In pT4, 1–3 CTC were found 2.7 and 1.7 times more frequently, 3 CTC 1.4 times more frequently than in pT1–2 and pT3, respectively (p ≤0.05). Presence of metastatic lesions increases the probability of CTC detection by the factor of 2.1: in metastases, >3 CTC were observed 60.1 times more frequently than in M0 (p ≤0.05). Expression of hsa-miR-143-3p and hsa-miR-26a-5p microRNA in CTC of patients with stage III colorectal cancer was respectively 2.5 and 5 times lower than in patients with stage II disease (p <0.05) and expression of hsa-miR-21-5p and hsa-miR-92a-3p microRNA was respectively 3.2 and 3 times higher (p <0.05). In CTC of patients with stage IV colorectal cancer, the relative level of expression of hsa-miR-143-3p and hsa-miR-26a-5p was respectively 4.6 and 5.3 times lower (p <0.05) compared to the level of expression in stage II disease, and hsa-miR-126-5p, hsa-miR-21-5p, hsa-miR-25-3p and hsa-miR-92a-3p expression levels were respectively 2.6, 4.6, 2.6 and 5.0 times higher (p<0.05) (statistically significant results).Conclusion. The level of microRNA expression in CTC can be used for differential diagnosis of regional and distant metastases.